Ketamine in the Treatment of Depression - Kaczmarska, Urszula Agnieszka; Cioch, Michał Jakub; Nowak, Julia; Woźniak, Aleksandra; Hermanowicz, Kamil; Najdek , Agnieszka; Oleksy , Daria; Komada, Dawid; Doman , Katarzyna; Mycyk, Marcin (Journal of Education, Health and Sport, 2025)
Introduction Depression is one of the most common mental illnesses. Over the course of a lifetime, several percent of the adult population suffers from depression. There are many treatments for depression like pharmacotherapy and psychotherapy. In this article, we wanted to focus on the effectiveness of ketamine in treating depression. Aim of study The study aimed to summarize the available knowledge on the use of ketamine in the treatment of depression. The epidemiology, etiology, side effects, and treatment methods, were summarized and described. Materials and method The literature available in the PubMed database was reviewed using the following keywords: “Ketamine”,” Depression”, and “Antidepressants”. Conclusion Without a doubt, ketamine has proven to be a new advocate for mental health research and therapeutics. After over half a century without novel targets for MDD (Major Depressive Disorder) treatment, the observation of ketamine’s rapid antidepressant effects in treatment-resistant depression has become a promising field that could represent a breakthrough in the understanding of MDD, and the possibility of reducing some of the major personal and global burden that depression is responsible for. It seems imminent then that a new era of different acting antidepressant strategies is upon us, and it is our responsibility to make a critical analysis of the potential benefits and harm inherent to novel therapeutics.